Clinical Indications Of Usheerasava An Experiential And Scientific View - Shripathi , Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Asavarishtas are formulations of Ayurveda which contain natural self-generated alcohol and can be preserved for longer time. Vasakarishta, Ashokarishta, Balarishta, Arjunarishta, Ashwagandharishta, Vidangarishta, and Khadirarishta are few Asavarishta preparations which are commonly used in general clinical practice. Usheerasava is one such preparation which is given in Paittika disorders. It is usually given in Raktapitta, Constipation, Menorrhagia, Metrorrhagia, Poly-menorrhea, Guda Gata Raktapitta, Hemorrhoids, Nasagata Raktapitta, Pleeha Vriddhi, and skin disorders. It contains Sheeta Virya (cold) drugs like Usheera, Chandana, Kumuda and Kamala which pacifies vitiated pitta in the body and relieves Pittaja disorders. The present paper highlights about the clinical indications of Usheerasava in an experiential and scientific view.